New constraints on elemental and Pb and Nd isotope compositions of South American and Southern African aerosol sources to the South Atlantic Ocean - Khondoker, R.; Weiss, D.; van de Flierdt, T.; Rehkamper, M.; Kreissig, K.; Coles, B. J.; Strekopytov, S.; Humphreys-Williams, E.; Dong, S.; Bory, A.; Bout-Roumazeilles, V.; Smichowski, P.; et al. (My University, 2018)
Improving the geochemical database available for characterising potential natural and anthropogenic aerosol sources from South America and Southern Africa is a critical precondition for studies aimed at understanding trace metal controls on the marine biogeochemical cycles of the South Atlantic Ocean. We here present new elemental and isotopic data for a wide range of sample types from South America and Southern Africa that are potentially important aerosol sources. This includes road dust from Buenos Aires and lichen samples from Johannesburg, soil dust from Patagonia, volcanic ash from the Andean volcanic belt, and aerosol samples from Sao Paulo. All samples were investigated for major (Al, Ca, Fe, Mg, Na, K, Mn) and trace element (Cd, Co, Cr, Cu, Ni, Pb, REE, Sc, Th, Y, V, Zn) concentrations and Nd and Pb isotopic compositions. We show that diagrams of (208)pb/(207)pb vs. epsilon(ND), Pb-208/Pb-207 vs. Pb/Al, 1/[Pb], Zn/Al, Cd/Al, Cu/Al, and epsilon(Nd) vs. Pb/Al, and 1/[Nd] are best suited to separate South American and South African source regions as well as natural and anthropogenic sources. A subset of samples from Patagonia and the Andes was additionally subjected to separation of a fine (< 5 mu m) fraction and compared to the composition of the bulk sample. We show that differences in the geochemical signature of bulk samples between individual regions and source types are significantly larger than between grain sizes. Jointly, these findings present an important step forward towards a quantitative assessment of aeolian trace metal inputs to the South Atlantic Ocean.
Keywords: isotopic and elemental composition; source characterisation; geochemical assessment; aerosol; south america; southern africa; south atlantic ocean